Understanding obstructive sleep apnea - Aini, Nur; Nguyen, Trung V.; Khairi, Sabiah (The Journal of Palembang Nursing Studies, 2024)
Obstructive sleep apnea (OSA) is defined by repeated episodes of partial or complete upper airway collapse, obstructing breathing during sleep. OSA is a dangerous health condition with high mortality and morbidity. Due to the rising prevalence of obesity, OSA is on the rise in developing countries. Nevertheless, the exact number of OSA prevalence among Indonesian people is unrecognized for several reasons; for instance, low awareness of sleep disorder issues, unawareness of the symptoms and impact of OSA, limited access to polysomnography examinations, and considering snoring as a common condition. Long-term health effects, decreased sleep quality, psychological issues, and cognitive impairment are all linked to untreated OSA. Nurses can contribute to the management of OSA by conducting screening and assessment, providing health promotion to patients, and coordinating with other healthcare providers. This paper explores the prevalence of OSA, society’s perception of OSA, diagnostic or screening procedures, and treatment options for the effective management of OSA.